Changes in Sports Activity After Periacetabular Osteotomy: A Qualitative and Quantitative Analysis. Issue 2 (February 2023) - Leopold, Vincent J.; Szarek, Adrian; Hipfl, Christian; Pumberger, Matthias; Perka, Carsten; Hardt, Sebastian; Löchel, Jannis
Background: Patients undergoing periacetabular osteotomy (PAO) for symptomatic developmental dysplasia of the hip are usually young and active with high functional demands. Those who participate in sports seek surgical therapy to resume or maintain sports activities. There is little evidence regarding the postoperative level of activity and the extent to which sports activity changes after PAO both qualitatively and quantitatively. Purpose: The aim of this study was to determine the change in activity level as measured using the University of California Los Angeles (UCLA) activity score and the changes in qualitative and quantitative sports activity. Study Design: Case series; Level of evidence, 4. Methods: This was a retrospective analysis of prospectively collected data of 123 hips in 111 patients who underwent PAO for developmental dysplasia of the hip between January 2015 and June 2017. UCLA activity score, International Hip Outcome Tool 12, and Subjective Hip Value, as well as practiced sports, frequency and duration of sports activity, and time to return to sports, were assessed. Eventual changes in practiced sports and reasons for those changes were recorded. Results: Of the participating patients, 85% were female and 15% were male. The mean patient age at the time of surgery was 27.7 ± 7.3 years. Mean follow-up was 63 ± 10 months. UCLA score (5.08 ± 2.44 vs 6.95 ± 1.74; P < .001), International Hip Outcome Tool 12 (41.4 ± 22.2 vs 72.6 ± 22.9; P < .001), and Subjective Hip Value (42.8 ± 24.3 vs 80.4 ± 17.8; P < .001) increased significantly from pre- to postoperatively. Significantly more patients participated in low-impact sports postoperatively (31.7% vs 52%; P = .001). Participation in high-impact sports decreased (42.3% vs 36.6%; P = .361). The overall sports activity rate increased significantly (78.8% vs 90.8%; P = .008). Quantitatively, sports frequency in times per week ( P < .001) as well as length of exercise per time ( P = .007) increased significantly. A total of 52 patients (42%) changed sports activities postoperatively. Of these, 35 (28.4%) reported having stopped previously practiced sports after surgery, while 17 (13.8%) reported having started new sports. Reasons for starting and stopping certain sports varied and included hip- and non–hip related ones. In only 2 cases was physician's advice given as a reason for changing the sport. Conclusion: Patients can improve their sports activity both qualitatively and quantitatively after PAO. However, a relevant proportion of patients adjusts their sports activities for a variety of hip-related and non–hip related reasons.